2021
DOI: 10.3348/kjr.2020.0311
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Abbreviated MRI and Full Diagnostic MRI in Distinguishing between Benign and Malignant Lesions Detected by Breast MRI: A Multireader Study

Abstract: Objective: To compare the performance of simulated abbreviated breast MRI (AB-MRI) and full diagnostic (FD)-MRI in distinguishing between benign and malignant lesions detected by MRI and investigate the features of discrepant lesions of the two protocols. Materials and Methods: An AB-MRI set with single first postcontrast images was retrospectively obtained from an FD-MRI cohort of 111 lesions (34 malignant, 77 benign) detected by contralateral breast MRI in 111 women (mean age, 49.8. ± 9.8; range, 28-75 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…A previous single-centre study, of 8 readers from the UK National Health Service Breast Screening Programme (NHSBSP), suggested that NHSBSP mammogram readers could be effectively trained to interpret abMRI with a single day’s one-to-one training [ 21 , 27 ]. Other international publications describe specific abMRI interpretation training for radiologists reading abMRI [ 1 , 28 , 29 ], but there is little published evidence evaluating abMRI interpretation training. To address this knowledge gap with formal evaluation of abMRI small-group training, our previous study’s one-to-one training [ 21 ] was adapted to create an electronic training package, delivered as single-day, small-group, in-person, hands-on workstation training.…”
Section: Introductionmentioning
confidence: 99%
“…A previous single-centre study, of 8 readers from the UK National Health Service Breast Screening Programme (NHSBSP), suggested that NHSBSP mammogram readers could be effectively trained to interpret abMRI with a single day’s one-to-one training [ 21 , 27 ]. Other international publications describe specific abMRI interpretation training for radiologists reading abMRI [ 1 , 28 , 29 ], but there is little published evidence evaluating abMRI interpretation training. To address this knowledge gap with formal evaluation of abMRI small-group training, our previous study’s one-to-one training [ 21 ] was adapted to create an electronic training package, delivered as single-day, small-group, in-person, hands-on workstation training.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Kuhl et al [6] proposed the concept of abbreviated MRI (AB-MRI), which consists of one pre-and one post-contrast acquisition and their derived images (first post-contrast-subtracted and maximum-intensity projection [MIP]). Following these initial studies, multiple studies have reported that the diagnostic accuracy of AB-MRI is equivalent to that of the conventional full diagnostic protocol of MRI (FDP-MRI), with shorter acquisition and reading times, thereby making it more cost-effective as a screening tool [7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…We also included second post-contrast images to our abbreviated protocol for detecting low-grade cancers. Kim et al also showed that using only the first post-contrast images could miss 15% of cancers (20).…”
Section: Discussionmentioning
confidence: 99%